Intramedullary versus Extramedullary Tibial Cutting Guides in Total Knee Procedures: Our Experience at King Abdulaziz University Hospital in Saudi Arabia - Lutf A. Abumunaser; Amre S. Hamdi; Faeq M.W. Sawaf (Journal of King Abdulaziz University: Medical Sciences, 2023)
The tibial component alignment is believed to be a key factor for the survivorship of total knee arthroplasty. But there is still controversy whether intramedullary or extramedullary cutting guidance is more accurate for tibial component alignment. This retrospective study aims to compare the accuracy of intramedullary and extramedullary tibial cutting guides in Total knee replacement. 88 Total knee replacements were carried out in 60 patients between January 2013 and April 2015. Out of 88 procedures 38 were in the intramedullary group and 50 in the extramedullary group. The tibial component alignment was evaluated by measuring the laterally formed angle between the transverse axis of the tibial component and the mechanical axis of the tibia. The tibial component angle was measured on postoperative long film X-rays of lower limb. The mean tibial component angle ± SD was 91.22 ± 2.74 for the intramedullary group, and 91.95 ± 2.34 (p = 0.184) for the extramedullary group. The normal tibial component angle values (88-92) was found in 52.6% in the intramedullary group and in 48% of the extramedullary group (p = 0.188). No statistically significant difference was found between the intramedullary and extramedullary tibial cutting guides with regard to the accuracy of the normal tibial component alignment.